PEMBELAJARAN VIRTUAL: MENINGKATKAN HASIL BELAJAR MATA KULIAH INSTALASI LISTRIK - Syamsul Mardan; Giatman Giatman; Syahril Syahril (Jurnal Dedikasi Pendidikan, 2021)
The quality of education can be improved by improving the ability of lecturers, improving the content of courses, improving the quality of learning and evaluation, providing adequate teaching materials, adequate facilities and infrastructure, etc. Among them, improving the quality of learning occupies a very important strategic position. A qualified learning process is expected to improve student learning outcomes. This research aims to improve students' understanding of basic electrical installation disciplines, especially the topics of home electrical installation planning. This is a classroom action research, including two cycles